(untitled) (Bangladesh Journal of Nuclear Medicine, 2016)
Background: There is no maximum limit for cumulative dose of I-131 for persistent disease in well-differentiated thyroid carcinoma (DTC) patients. However, most remissions are obtained with cumulative activity equal to or lower than 600 mCi (22 GBq). On the other hand a significantly increased risk of leukemia and secondary cancers has been reported with high cumulative dose of I-131 (? 600 mCi). Above this cumulative activity further radioiodine therapy should be taken on an individualized basis. Objective: The aim of the study was to see the outcome of patients with well differentiated thyroid carcinoma receiving a cumulative doses (CDs) of ? 600 mCi I-131. Patient and Method: A retrospective study of 72 patients with DTC receiving a CDs of ?600 mCi I-131 in the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Dhaka during the period of January 1994 up to December 2007 was carried out. Initially all patients were treated by thyroidectomy followed by radioiodine therapy as adjusted by standard protocol. The mean period of follow up was 8.9 ± 6 years. From the medical files, age, gender, histopathological variant, thyroid remnant and radio ablation doses, follow up data were recorded. Age was further categorized as <45 and ?45 years. Thyroid bed remnant was designated as significant if the thyroid bed uptake was ?5% after surgery. Dose was categorized in ?5 dose and > 5 doses to find its association with status on last follow up. Disease free (DF) was established as: undetectable or suppressed serum Tg levels <2.0 ng/mL and stimulated serum Tg level <10 ng/mL, two consecutive negative whole body scans. Results: A total of 38 patients had papillary carcinoma, eight had follicular variant of papillary carcinoma and 26 had follicular carcinoma. Age range at diagnosis was nine to 72 years. There were 22 males and 50 females giving a M: F ratio of about 1:2. Among the 72 patients 25 patients had lymph node metastases, eight had lung metastases and 20 had bone metastases at presentation. Twenty-one patients died during the whole observation period and 20 of them were cancer related. Two patients developed second malignancy. Conclusion: DTC patients with follicular variant, ? 45 years of age, having bone metastasis and significant thyroid remnant have less favourable outcome in spite of high cumulative doses of radioiodine. DTC patients with higher TNM stage and bone metastasis require higher and more radioiodine doses. Bangladesh J. Nuclear Med. 17(2): 114-119, July 2014